Atypical presentation of occult congenital diaphragmatic hernia as intermittent obstructive symptoms: A case report - Connor V. Haynes; Carly T. Thaxton; Matthew P. Shaughnessy; David H. Stitelman (Journal of Pediatric Surgery Case Reports)
Introduction: Congenital diaphragmatic hernias (CDH) diagnosed beyond one month of life are rare and designated late-onset. Late-onset CDH can present with a variety of clinical manifestations including respiratory and gastrointestinal symptoms, which may be acute onset or long-standing chronic issues. Case presentation: A 32-month-old boy with a five-month history of obstructive bowel symptoms was brought to the emergency department due to acute respiratory distress and abdominal pain. He was born at 41w1d with no prenatal suspicion of congenital anomalies. At the age of 27 months, the previously healthy patient with normal stooling patterns presented with a picture of bowel obstruction and was subsequently admitted three times over the next five months, with a maximum stay of eight days, due to ongoing obstructive symptoms. Multiple abdominal and chest radiographs during this period did not reveal an obvious structural etiology. Upon his respiratory distress presentation, repeat radiography revealed bowel loops in the left hemithorax with rightward mediastinal shift. Laparoscopy and thoracoscopy demonstrated a posterior left diaphragmatic hernia with omentum adherent to lung. Laparotomy was performed for reduction and suture repair of the diaphragm. Omentum fixed to the splenic flexure of the colon resulted in a fibrotic band of scar tissue and bowel caliber change. These bands were lysed. The post-operative course was uneventful, and the patient has maintained normal bowel movements without abdominal pain for three months. Conclusion: Late-onset congenital diaphragmatic hernia must be included in the differential diagnosis of children who present with new-onset acute intestinal obstruction.